THE RELATIONSHIP BETWEEN PSYCHOSOCIAL STRESS, ENERGY INTAKE, CALCIUM AND THE NUTRITIONAL STATUS OF THE FEMALE ADOLESCENTS IN SURAKARTA - Nugroho, Riezky Faisal; Hanim, Diffah; Dewi, Yulia Lanti Retno (Jurnal Keperawatan Soedirman, 2018)
ABSTRACTFemale adolescents are at risk of nutrient deficiency. Adolescent stress can arise due toÃ‚Â  the social environmental factor called psychosocial stress. The purpose of this study was to determine the relationship between psychosocial stress, energy intake, calcium and the nutritional status of the female adolescents in Surakarta. The design of the research used was observational analytic with a cross-sectional design. The sample of this study was comprised of 166 students from 2 junior high schools in Surakarta City. The data of the psychosocial stress were collected using a Psychosocial Stress Assessment Instrument (IPSP). Then, the data of the energy intake and calcium were collected using 2x24-hour-recall questionnaire and nutrisurvey, and the nutritional status data were collected using the measurements of body weight (kg) and height (m). The data were then analysed using chi square. The results showed that there was a relationship (p < 0,05) between the psychosocial stress, energy intake, calcium and the nutritional status of the female adolescents in Surakarta.Keywords: Psychosocial Stress, Energy Intake, Calcium, Nutritional Status, Female Adolescent